Association of Adverse Perinatal Outcome with Oligohydramnios during Third Trimester of Pregnancy - Sadia Mustafa, Mahwish Saif, Maliha Amjad, Faiza Iqbal (Pakistan Journal of Medical & Health Sciences, 2023)
Background: For the growth and development of the unborn child, amniotic fluid is absolutely necessary. Strong interactions between the fetus, placenta, and parts of the mother are given their volume1. Oligohydramnios is defined as having an amniotic fluid index (AFI) <5th percentile or AFI 5 cm during pregnancy and no water at a depth of 23 cm before the cornea. This is a common problem that occurs in 35% of pregnancies during childbirth2. Aim: To determining the correlation between oligohydramnios in pregnant women who are late in pregnancy (3rd trimester) and adverse birth outcomes such as partial surgery, decreased Apgar score, and lower birth weight. Study design: Cohort study Study set up: Obstetrics and Gynecology Department, Fatima Memorial Hospital Lahore. Study period: six months starting15-01-2022 to 14-07-2022 Methods: 242 females were enrolled. Two groups of participants were created: group II had normal AFI and group I had oligohydramnios. Females given intra venous fluids to group I after ruling out any contra indication. The perinatal result was then documented. SPSS version 20 was used to enter and evaluate all of the gathered data. Results: In exposed group the mean age was 27.79±6.72 years, whereas in unexposed group the mean age was 28.25±6.77 years. The C-section was done in 124(51.2%) females. RR = 0.693 [1.25-3.49] While the Low Birth Weight and poor APGAR score has shown protective effect. Practical implication: Oligohydramniosmeans decreased amniotic fluid around the fetus. There is deficiency of amniotic fluid < 200 ml at a time. Approximately 8-10% of pregnant ladies may have decreased level of amniotic fluid but 5% have been confirmed diagnosis of oligohydramnios. Conclusion: So complications of surgery are directly related to the severity of oligohydramnios in pregnant women while low birth weight and poor APGAR scores has shown protective effect in women presented in last trimester of pregnancy. Keywords: Oligohydramnios, Low Birth Weight, Perinatal Outcome, APGAR SCORES, Pregnancy